2012
DOI: 10.1590/s0100-204x2012001200013
|View full text |Cite
|
Sign up to set email alerts
|

Chemical attributes of a Hapludox soil after nine years of pig slurry application

Abstract: -The objective of this study was to evaluate the pig slurry application effects on chemical attributes of a Hapludox soil managed under no-tillage system. Treatments consisted of 50, 100 and 200 m 3 ha -1 per year of pig slurry application, and a control with replacement of P and K exported through harvested grains. Attributes related to soil chemical reaction, exchange complex, and nutrient contents were determined in soil samples collected in the ninth year of experimentation from 0-0.025, 0.025-0.05, 0.05-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 17 publications
2
27
0
4
Order By: Relevance
“…According to the authors, the levels of available Cu and Zn in the 0-0.10 m soil layer of the treatment with the highest rate of organic fertilizer were, on average, 12 and 24 times higher, respectively, than in the control. Veiga et al (2012) found that continuous application of high pig slurry rates, up to 200 m 3 ha -1 yr -1 on the soil surface, resulted in sharp increases in P, Cu and Zn concentrations to a depth of 0.2 m. These authors also reported a reduction in soil pH with the application of organic fertilizer, and attributed it to the acidification process of nitrification.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…According to the authors, the levels of available Cu and Zn in the 0-0.10 m soil layer of the treatment with the highest rate of organic fertilizer were, on average, 12 and 24 times higher, respectively, than in the control. Veiga et al (2012) found that continuous application of high pig slurry rates, up to 200 m 3 ha -1 yr -1 on the soil surface, resulted in sharp increases in P, Cu and Zn concentrations to a depth of 0.2 m. These authors also reported a reduction in soil pH with the application of organic fertilizer, and attributed it to the acidification process of nitrification.…”
Section: Resultsmentioning
confidence: 95%
“…There are several reports in the literature of increased levels of soil nutrients after pig slurry application under field conditions (Ceretta et al, 2003;Scherer et al, 2010;Girotto et al, 2010;Veiga et al, 2012). However, these studies used organic fertilizers with a higher dry matter content compared with the biofertilizer used in this experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the sequential addition of pig slurry may contribute to the improvement or maintenance of some chemical (VEIGA et al, 2012) and physical characteristics of the soil (AGNE & KLEIN, 2014) and increase the availability of food for the soil fauna owing to the addition of large quantities of organic compounds, an increase in the density of organisms in the soil is to be expected. Thus, with adequate management and dosage, pig slurry may contribute to increased soil quality, promoting ecological equilibrium by reusing agricultural waste without polluting the environment (ALVES, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The application of pig manure as slurry (PS) increases the levels of N, P, K, Ca and Mg in the soil (Scherer et al, 2007;Veiga et al, 2012b) and in the crops (Choudhary et al, 1996;Cassol et al, 2012;Sartor et al, 2012;Scherer et al, 2012). Due to the low content of nutrients present in this manure (Scherer et al, 1996), the use of large volumes is usually necessary to provide enough amounts of plant nutrients.…”
Section: Introductionmentioning
confidence: 99%